Cancer Immunotherapy Meets Oncology In Honor of Christoph Huber - Britten, Cedrik Michael; Kreiter, Sebastian; Diken, Mustafa; Rammensee, Hans-Georg.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book provides a comprehensive update on the state of the art in cancer immunology, which has rapidly evolved from a field of clinical research into an established discipline of oncology. The key recent developments in immuno-oncology are all covered, from the ever-changing immunological and regulatory frameworks to the most promising therapeutic concepts. Themes include combination therapies and personalized medicine, as well as identification of biomarkers to guide the clinical development of new approaches and to pinpoint the optimal treatment for each patient. The book acknowledges the continuing dynamic nature of the field as reflected in the development of next-generation immunotherapies that are already in clinical testing.   Cancer Immunotherapy Meets Oncology is dedicated to the lifetime achievements of Christoph Huber, founder and chair of the Association for Cancer Immunotherapy (CIMT). It is also a tribute to those researchers and clinicians who are striving to develop novel diagnostics and tailored immunotherapies for the benefit of cancer patients.
Immunological and Regulatory Framework for Immuno-Oncology: From Basic Immunology to New Therapies for Patients -- How T cells single out tumor cells: 'and that has made all the difference' -- Tregs and Immune Inhibition -- Regulatory Landscape for Cancer Immunotherapy -- Immunoguiding -- Onco-Immunology Framework and Immunomodulatory Antibodies -- Immunotherapies: Peptide-based Vaccines and HPV Malignancies.- Dendritic cell based cancer vaccines.- RNA Vaccines and Personalized Medicine Approaches.-Antibody Therapy in Oncology.- Engineered Antibodies to Engage Immune Cells to the Tumor -- TCRs and TCR Therapy -- CAR Therapy.- Cancer Entities: Melanoma -- Prostate Cancer/Sipuleucel and RNA Vaccines -- Recent advances in the immunotherapy of renal cell cancer and other solid tumors -- Gastric Cancer -- NSCLC -- Breaking tolerance by allogeneic lymphocyte therapy.- Biomarkers: Exploring Immunogenic Cell Death for Patient Benefit -- Circulating Tumor Cells -- Genomics Meets Oncology -- Featured Chapters: Oncolytic Viruses -- Pharma View on Immunotherapy -- Final Remarks.
Keywords: Oncology .; Cancer research; Pharmacology; Immunology; Oncology; Cancer Research; Pharmacology/Toxicology.; Immunology